Glass-Ceramic Foams from "Weak Alkali Activation' and Gel-Casting of Waste Glass/Fly Ash Mixtures - Romero, Acacio Rincon; Toniolo, Nicoletta; Boccaccini, Aldo R.; Bernardo, Enrico (Materials, 2019)
A weak alkali activation' was applied to aqueous suspensions based on soda lime glass and coal fly ash. Unlike in actual geopolymers, an extensive formation of zeolite-like gels was not expected, due to the low molarity of the alkali activator (NaOH) used. In any case, the suspension underwent gelation and presented a marked pseudoplastic behavior. A significant foaming could be achieved by air incorporation, in turn resulting from intensive mechanical stirring (with the help of a surfactant), before complete hardening. Dried foams were later subjected to heat treatment at 700-900 degrees C. The interactions between glass and fly ash, upon firing, determined the formation of new crystal phases, particularly nepheline (sodium alumino-silicate), with remarkable crushing strength (6 MPa, with a porosity of about 70%). The fired materials, finally, demonstrated a successful stabilization of pollutants from fly ash and a low thermal conductivity that could be exploited for building applications.
CRIS-Team WoS Importer:2019-03-26
Keywords: Fly ash; Alkali activation; Inorganic gel casting; Glass-ceramic foams; Waste glass